Patent Ever Greening - Kumar Mohapatra, Chinmaya (International Journal of Psychosocial Rehabilitation, 2025)
Patent is an exclusive privilege to reward the true and first inventors of new inventions. To be patentable, an invention must be novel, involving inventive step and of industrial application. Theoretically patents exist to promote the diffusion of innovative knowledge. The patent system provides necessary incentives for investment in research and encourages inventors to engage in new lines of R & D, thus it stimulating further creativity. It is considered as exclusive right and not as a monopoly, because in the scheme of patents there are inbuilt checks and balances to prevent the abuse of patents such as compulsory licensing, permitted use etc. However, the recent trend in the patent system shows that there is a tendency to evergreen the patent rights, especially in the pharmaceutical sector, by making trivial modifications and changes. Drug companies generally do ever-greening, by filing new patent applications, tweaking existing molecules to show novelty. Ever-greening of patent is a phrase used to label practices that have developed in certain jurisdictions wherein a trifling change is made to an existing product, and claimed as a new invention. The present paper discusses about the patents with a special emphasis on ever-greening of patents. The landmark judicial decision in Novartis A G v. Union of India will also be analyzed.